Web-Based Announcement System for UTP : "ANNOUNCECLICK'ATEL" - Mohd Radzi, Nor Shahila (Universiti Teknologi Petronas, 2004)
Basically the main objective of this project called Web-based Announcement System is to automate the manual wayof conveying announcements either academic or event updates in Universiti Teknologi PETRONAS (UTP) campus and provide an effective way of prompting students on the announcements. Furthermore, the proposed system will enable the lecturers, IT administrators, Webmaster to upload announcements and to prompt students via short messages (SMS) and student personal email. Another objective of this project is to provide a web-based announcement system that can encourage regular or frequent access by students andthe announcements willbe able to be delivered effectively. Currently, students received most of the academic announcements such as current event updates, class cancellation or changes of test schedule verbally. In addition to that, if there is an important event to be held in UTP, the common medium of notification used is notice boards, posters or eLearning. Even though there is an eLeaming available, still the announcements delivery management is not so effective due to the accessibility of the system application. As far as the final year project is concern; the project will be focusing on the contentmanagement aspect that shouldbe considered to develop an announcement system andhowit canbe accessible via SMS and e-mail which will provide a two-way communication between the sender and the recipient. The methodology that will be used here is Waterfall model which include Project definition and planning, analysis and design, development, unit testing and testing, and implementation and rollout. The findings of this project will be, the students will be able to receive the announcement via SMS and can have a two-way communication with the lecturers. Besides the updates will also be given via SMS and it will provide an automatic answer.